Acceptability and Protein Content of Cookies Made from Cork Fish Flour and Cheese as an Effort to Prevent Chronic Energy Deficiency in Adolescent Girls - Maisyah Setya Ardhani; Taufiqurrahman; Riezky Faisal Nugroho; Ani Intiyati (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Chronic Energy Deficiency is one of the health problems faced by adolescents due to nutritional deficiencies. Objective, To determine the acceptability of cork fishmeal and cheese-based cookies as an effort to prevent Chronic Energy Deficiency in adolescent girls. This study used Pre-Experimental design with three different formulations: CG1 (27 g wheat flour), CG2 (10 g wheat flour, 5 g cork fish, 12 g cheese), and CG3 (10 g wheat flour, 8 g cork fish, 9 g cheese). A total of 750 grams of samples were organoleptically tested using a hedonic scale in the laboratory of the Nutrition Department of Surabaya Polytechnic and analyzed with the Kruskal Wallis test and Mann Whitney test if there was a significant difference (p-value <0.05). Showed significant differences in color (p-value 0.041) and aroma (p-value 0.036) indicators, but there were no significant differences in texture (p-value 0.367) and taste (p-value 0.430). Formulation CG2 with 8.14% protein content was most favored by the panelists. Formulation CG2 was considered the best and qualified as a snack food. Suggestions It is hoped that the formulation of cookies based on cork fish flour and cheese can be improved and developed again for the results of a better formula.